The order to us solve is:
- Parentheses
- Multiplication
- Sum and subtraction
Let's go:
Therefore, the result is 62.2.
Answer:
Step-by-step explanation:
Multiplying x+6y=-3 with 2 so its equal to first eqn,
Eliminating,
2x + 3y = 3 (1)
2x +12y = -6 (2) (because subtracting)
------------------
-9y =9
∴y=-1
eq. y in 1
2x -3=3
2x=3+3
x=6/2
=3
Pls mark me brainliest
Answer: (0,-4)
explanation: write in vertex form and use this form to find the vertex ( h , k )
Answer:
7*5 + -29
Step-by-step explanation:
She makes 7 payments of 5 to the store
7*5
Then she gets 29 dollars back so that would be negative
+ -29
7*5 + -29
35 -29
She has paid 6 dollars to the store
Answer:
Half; twice
Step-by-step explanation:
In a circle, the radius is said to be the distance from the center of the circle to any point on the edge of the circle, it is denoted as "r". The radius is called a radii if it is more than one.. The radius of a circle is half the length of the diameter of a circle because the diameter of a circle is the distance of the line that passes through the center of a circle touching both edges of the circle. It is denoted as "d".
Thus,
2r = d
r = d/2
For example, if the radius of a circle is 10cm, the diameter of the circle will be calculated as: d = 2 * 10 = 20cm. Which means if the radius is 10cm, diameter will be 20cm.
Therefore, the radius of a circle is half the length of its diameter. the diameter of a circle is twice the length of its radius